Dealing with ambiguity: Israeli physician's attitudes and practices regarding pre-exercise certificates: a questionnaire study. Issue 1 (December 2016) - Hoffman, Robert; Golan, Ron; Vinker, Shlomo
Abstract Background It has become clear in recent years that a healthy lifestyle, including physical exercise is crucial for health maintenance. Nevertheless, most people do not exercise regularly. Physician intervention is beneficial in increasing patient exercise. In Israel, the 1994 "Sports Law" regarding exercising in a gymnasium requires a physician's written authorization, but does not direct the physicians what they should ascertain before issuing the certificate. This pre-exercise certificate has been widely discussed in Israel over the last year as the law is to be revised to enable using a modification of the PAR-Q+ (Physical Activity Readiness questionnaire) patient questionnaire as a screening tool. This will leave the requirement for a pre-exercise certificate for a less healthy population, yet without clear instructions to the primary care physician on criteria for ascertaining fitness. Our aim was to evaluate how primary care physicians deal with the ambiguity of defining health criteria for issuing exercise authorization/certificate. Methods We used an anonymous ten-item attitude/knowledge multiple choice questionnaire with an additional 13 personal/education and employment questions. We assessed each potential predictor of physician attitude and knowledge in univariate models. Results 135 useable questionnaires were collected. Of these, 43.7 % of the doctors will provide the pre-exercise certificate to all their patients; 63 % were aware of their HMO/employers guidelines for issuing certificates; 62 % stated they complied with these guidelines, and 16 % stated they did not follow them. In addition, 70 % of the physicians reported regular exercise themselves, an average of 4.12 h/week. These physicians tended to provide the pre-exercise certificate to all patients unconditionally, as compared to physicians that did not exercise regularly. (46 % vs. 14.5 %, p  < 0.01) Conclusions Most Israeli primary care physicians will provide the required certificate allowing their patients to exercise in the gym. There is a wide variation as to what physicians check before providing the certificate. The modification of the law has made the need for standardization of the nature of what is expected of primary care physicians more urgent. A large portion of physicians exercise on a regular basis – and exercising physicians are more positive regarding pre-exercise certificates. Our study clearly shows a gap in knowledge transfer; and we call for a standardized approach to pre-exercise certificates utilizing computerized patient medical files.